IMPLEMENTASI PROJECT BASED LEARNING, CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KOMPETENSI MAHASISWA - Fatimah, Annisa; Magdalena, Marlina; Suryadi, Suryadi; Kristanti, Ima (ITB AAS Indonesia Surakarta, 2024)
The aim of this research is to implement a learning model during lectures that integrates Project Based Learning (PjBL) and Contextual Teaching and Learning (CTL) in the Computer Accounting course. This learning strategy makes it possible to produce qualifications for graduates' abilities starting from their attitudes, knowledge and skills in accordance with national higher education standards. It is proven that through the combination of PjBL and CTL, students can relate the material to real world situations, thus motivating students to make connections between knowledge and application in real life using projects as a medium. Student involvement in this project is their